Protective effects of the compounds isolated from the seed of Psoralea corylifolia on oxidative stress-induced retinal damage - Kim, Kyung-A; Shim, Sang Hee; Ahn, Hong Ryul; Jung, Sang Hoon (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2013)
The mechanism underlying glaucoma remains controversial, but apoptosis caused by increased levels of reactive oxygen species (ROS) is thought to play a role in its pathogenesis. We investigated the effects of compounds isolated from Psoralea corylifolia on oxidative stress-induced cell death in vitro and in vivo. Transformed retinal ganglion cells (RGC-5) were treated with L-buthione-(S,R)-sulfoximine (BSO) and glutamate in the presence or with pre-treatment with compound 6, bakuchiol isolated from P. corylifolia. We observed reduced cell death in cells pre-treated with bakuchiol. Moreover, bakuchiol inhibited the oxidative stress-induced decrease of mitochondrial membrane potential (MMP, Delta Psi m). Furthermore, while intracellular Ca2+ was high in RGC-5 cells after exposure to oxidative stress, bakuchiol reduced these levels. In an in vivo study, in which rat retinal damage was induced by intravitreal injection of N-methyl-D-aspartate (NMDA), bakuchiol markedly reduced translocation of AIF and release of cytochrome c, and inhibited up-regulation of cleaved caspase-3, cleaved caspase-9, and cleaved PARP. The survival rate of retinal ganglion cells (RGCs) 7 days after optic nerve crush (ONC) in mice was significantly decreased; however, bakuchiol attenuated the loss of RGCs. Moreover, bakuchiol attenuated ONC-induced up-regulation of apoptotic proteins, including cleaved PARP, cleaved caspase-3, and cleaved caspase-9. Bakuchiol also significantly inhibited translocation of mitochondrial AIF into the nuclear fraction and release of mitochondrial cytochrome c into the cytosol. These results demonstrate that bakuchiol isolated from P. corylifolia has protective effects against oxidative stress-induced retinal damage, and may be considered as an agent for treating or preventing retinal degeneration. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: OPTIC-NERVE CRUSH; GANGLION-CELL DEATH; QUANTITATIVE-ANALYSIS; GLAUCOMA; NEUROPROTECTION; GLUTAMATE; CONSTITUENTS; ANTIOXIDANT; FINGERPRINT; MECHANISMS